Is International Trade Always Beneficial to Labor Markets? A Case Study from Egypt - Raymond Robertson; Mexico Alberto Vergara Bahena; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2022)
Egypt's industries heavily rely on imported goods for production. Thus, an increase in imports could have a potentially positive effect on the labor market as it means more inputs for the production of exporting goods. Alternatively, minimal backward linkages in global value chains (GVCs) could also mean that increasing imports substitute for domestic production and thus, lost employment opportunities. This paper evaluates the relationship between regional trade agreements using a gravity model and import flows to test whether rising imports impacted wages, informality, and female labor force participation using the Bartik (1991) approach. Our results suggest that imports are not to blame for disappointing labor market outcomes in Egypt.
Keywords: F1; C1; 330; imports; trade; labor market; informality; econometrics; bartik; Egypt